ANALISIS KINERJA MENGAJAR GURU SMA TARUNA MANDIRI PEKANBARU - Maria Artha Nadeak; Sumarno Sumarno; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to analyse teacher performance in making lesson plan, analyse teacher performance in implementing lesson plan, and analyse teacher performance in carrying out evaluation of learning. This research was held at Taruna Mandiri Pekanbaru Senior High School in May until June 2017. The subject of this research is the teacher of Taruna Mandiri Pekanbaru Senior High School in the academic year 2017/2018. In the data collection using questionnaires, interviews and documentation.the result show of the study known that the teaching performance of Taruna Mandiri Pekanbaru Senior High School teacher has an average in the high level category (79.2%). A total of 12.7% in very high category, 71% in high category, 16% in enough category and 0.3% in low category.Keyword: Analyse, Teacher Performance